The girl in the torch - Sharenow, Rob (Balzer + Bray, an imprint of HarperCollinsPublishers, 2015)
After her father is killed in a pogrom, twelve-year-old Sarah and her mother immigrate to America--but when her mother dies before they get through Ellis Island, and the authorities want to send her back to the old country, Sarah hides in the torch of the Statue of Liberty.